2018
DOI: 10.1002/anie.201711429
|View full text |Cite
|
Sign up to set email alerts
|

A Non‐Competitive Inhibitor of VCP/p97 and VPS4 Reveals Conserved Allosteric Circuits in Type I and II AAA ATPases

Abstract: AAA ATPases have pivotal functions in diverse cellular processes essential for survival and proliferation. Revealing strategies for chemical inhibition of this class of enzymes is therefore of great interest for the development of novel chemotherapies or chemical tools. Here, we characterize the compound MSC1094308 as a reversible, allosteric inhibitor of the type II AAA ATPase human ubiquitin-directed unfoldase (VCP)/p97 and the type I AAA ATPase VPS4B. Subsequent proteomic, genetic and biochemical studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…The crystal structures of mammalian VPS4B and its yeast ortholog show similarities in their ATPase domains (Scott et al, 2005;Xiao et al, 2007;Hartmann et al, 2008;Inoue et al, 2008;Sun et al, 2017). Recent attempts to develop inhibitors for VCP/p97 (a distinct member of the type II AAA + ATPase family, overexpressed in many cancers) identified two compounds that inhibit yeast VPS4 (Zhang et al, 2016) and human VPS4B (Pohler et al, 2018). Even though the low selectivity of these molecules excludes their usage in the VPS4A+B synthetic lethality-based approach, it confirms the druggability of VPS4 and yields optimism for the future development of a selective VPS4 inhibitor.…”
Section: Of 21mentioning
confidence: 99%
“…The crystal structures of mammalian VPS4B and its yeast ortholog show similarities in their ATPase domains (Scott et al, 2005;Xiao et al, 2007;Hartmann et al, 2008;Inoue et al, 2008;Sun et al, 2017). Recent attempts to develop inhibitors for VCP/p97 (a distinct member of the type II AAA + ATPase family, overexpressed in many cancers) identified two compounds that inhibit yeast VPS4 (Zhang et al, 2016) and human VPS4B (Pohler et al, 2018). Even though the low selectivity of these molecules excludes their usage in the VPS4A+B synthetic lethality-based approach, it confirms the druggability of VPS4 and yields optimism for the future development of a selective VPS4 inhibitor.…”
Section: Of 21mentioning
confidence: 99%
“…In principle, chemical inhibitors of AAA proteins can be identified that target either the nucleotide-binding site or an allosteric site. An allosteric inhibitor-binding site has been characterized for VCP and the vacuolar protein sorting-associated protein 4 (VPS4) 15,16 . However, it is unclear if an equivalent site exists in other AAA proteins.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Several inhibitors of the D2 ATPase domain of p97 are available. [15][16][17][18][19][20][21] The most used p97 inhibitors identified recently, DBeQ, NMS-873 and MSC1094308 16,19,20 were isolated by screening compounds that inhibit the ATPase activity in vitro. Since p97 participates in a wide range of cellular processes, treatment with these drugs cause major cellular defects, including cell death.…”
Section: Introductionmentioning
confidence: 99%